The use of Marketing Technology in Stock Firms Based on Insourcing and Outsourcing Strategy - Kongcharoen, Chaknarin; Mueangkhot, Thanyalak (Journal of Applied Informatics and Technology, 2026)
Marketing technology (MarTech) is becoming increasingly important for businesses and marketers. Firms use MarTech tools and technologies to support marketing activities. This study attempts to understand how marketing technology is used in firms and to explore research evidence regarding how MarTech tools enhance marketing functions. Data were collected from 100 firms listed on the Stock Exchange of Thailand. The data were analyzed to classify 53 MarTech tools into 22 MarTech categories. The study classifies MarTech based on insourcing–outsourcing information technology and the marketing mix framework. The results identify three dimensions of MarTech tools: insourcing, outsourcing, and hybrid sourcing. Finally, the study provides recommendations and future research directions for the adoption of marketing technology practices. This paper provides a comprehensive literature review and proposes a classification of marketing technology based on an insourcing–outsourcing perspective.